Effect of a Mediterranean dietary pattern and Vitamin D levels on dry eye syndrome - Galor, Anat (2014)
PURPOSE: To evaluate the association between a Mediterranean dietary pattern (MeDi) and Vitamin D levels on dry eye syndrome (DES) METHODS: DESIGN: Cross-sectional study. PARTICIPANTS: Male patients seen in the Miami Veterans Affairs eye clinic with normal eyelid, corneal, and conjunctival anatomy were recruited to participate in the study. TESTING: Patients filled out the 2005 Block Food Frequency Questionnaire (FFQ) and the Dry Eye Questionnaire 5 (DEQ5) and underwent measurement of tear film parameters. Serum level of 25-hydroxy vitamin D was also measured. MAIN OUTCOME MEASURES: Association between MeDi, Vitamin D levels and dry eye syndrome. RESULTS: 247 men underwent DES testing. The mean patient age was 69 years (range 55 to 95). Using latent class analysis (LCA) to categorize the presence/absence of disease and quantify its severity, we found that adherence to the MeDi was positively associated with the risk both of having DES (odd ratio (OR) 1.25, 95% confidence interval (CI) 1.06–1.47) p=0.007) and with increasing disease severity. Vitamin D levels were not significantly associated with presence or severity of disease. However, higher levels of vitamin D were associated with decreased DES symptoms, with a −1.24 decrease in median DEQ5 score for every 10 unit increase in Vitamin D levels (p=0.01). CONCLUSIONS: Adherence to the MeDi was not associated with a beneficial effect on DES. Higher vitamin D levels had a small, but favorable effect on DES symptoms.